Competing kingdoms: women, mission, nation, and the American Protestant empire, 1812 - 1960 - Reeves-Ellington, Barbara; Sklar, Kathryn Kish; Shemo, Connie Anne (American encounters / global interactions, 2010)
Women's mission in historical perspective : American identity and Christian internationalism / Jane H. Hunter -- Woman, missions, and empire : new approaches to American cultural expansion / Ian Tyrrell -- Canonizing Harriet Newell : women, the evangelical press, and the foreign mission movement in New England, 1800/1840 / Mary Kupiec Cayton -- An unwomanly woman and her sons in Christ : faith, empire, and gender in colonial Rhodesia, 1899/1906 / Wendy Urban-Mead -- "So thoroughly American": Gertrude Howe, Kang Cheng, and cultural imperialism in the Woman's Foreign Missionary Society, 1872/1931 / Connie Shemo -- From redeemers to partners : American women missionaries and the "woman question" in India 1919/1939 / Susan Haskell Khan -- Settler colonists, "Christian citizenship," and the Women's Missionary Federation at the Bethany Indian Mission in Wittenberg, Wisconsin, 1884/1934 / Betty Ann Bergland -- New life, new faith, new nation, new women : competing models at the door of Hope Mission in Shanghai / Sue Gronewold -- "No nation can rise higher than its women" : the women's ecumenical missionary movement and Tokyo Woman's Christian College / Rui Kohiyama -- Nile mother: Lillian Trasher and the orphans of Egypt / Beth Baron -- Embracing domesticity : women, mission, and nation building in Ottoman Europe, 1832/1872 / Barbara Reeves-Ellington -- Imperial encounters at home : women, empire, and the home mission project in late nineteenth-century America / Derek Chang -- African American women missionaries in the Congo, 1887/1899 : the confluence of race, culture, identity, and nationality / Sylvia M. Jacobs -- "Stepmother America" : the Woman's Board of Missions in the Philippines, 1902/1930 / Laura R. Prieto -- Conclusion : doing everything: religion, race, and empire in the US Protestant women's missionary enterprise, 1812/1960 / Mary A. Renda